Happy by design : a guide to architecture and mental wellbeing - Channon, Ben (RIBA Publishing, 2018)
Can good design truly make us happier? Given that we spend over 80% of our time in buildings, shouldn't we have a better understanding of how they make us feel? This book explores the ways in which buildings, spaces and cities affect our moods. It reveals how architecture and design can make us happy and support mental health, and explains how poor design can have the opposite effect. Presented through a series of easy-to-understand design tips and accompanied by beautiful diagrams and illustrations, Happy by Design is a resource for architects, designers and students, or for anybody who would like to better understand the relationship between buildings and happiness.